The role of hormone therapy in the lives of menopausal women - Putyński, Leszek; Janicka, Karolina (Menopause Review/Przegląd Menopauzalny, 2011)
The aim of the conducted study was to evaluate the efficiency of the hormone therapy used by women at the menopausal stage, i.e. the assessment of differences in frequency and intensity of menopausal symptoms in women subject to hormone therapy in comparison to those who are not. Material and methods: The study was conducted among 60 women (30 women with menopause using hormone therapy and 30 women with menopause without any treatment) aged from 45 to 70 years. The frequency and intensity of menopausal symptoms were measured with the scale of Greene and the Women’s Health Questionnaire (WHO) by M. Hunter. Results: The results showed that there were differences in the occurrence and severity of menopausal symptoms between women subjected to hormone therapy and those who do not use this type of treatment. Women with no hormone therapy demonstrate more menopausal symptoms with more severity in comparison to their counterparts with hormonal treatment. Conclusion : The use of hormonal therapy should be considered legitimate, as it significantly reduces the undesirable symptoms of menopause and it may facilitate the everyday well-being of women